No Association Between Maternal Post-partum Depression and Vaccination Uptake of Infants: A Matched Cohort Study in a Large Health Maintenance Organization Database in Israel - Zaikin, Ariela; Koren, Gideon; Chodick, Gabriel; Grossman, Zachi (Frontiers in Pediatrics, 2022)
Background Maternal post-partum depression is one of the most common medical complications around childbirth. One of its consequences is a possible association with children's receipt of preventive health care, including immunization. This study aimed to explore the association between maternal postpartum depression and children's immunization rates. Methods A retrospective cohort study of Maccabi Healthcare Services (HMO) members comparing immunization rates between children born between 2006 and 2019 to mothers with post-partum depression and children born to mothers with no documented depression. Post-partum depression was assessed by Edinburgh Postnatal Depression Scale, a 10-item questionnaire considered the screening tool of choice in Israel for early Post-partum detection. 1:1 matching was conducted according to criteria: age of the mother ± 2 years, child's year of birth, the newborn baby's gender, the baby's birth order and socioeconomic index. The primary outcome was defined as non-vaccination and the exposure was defined as depression. A sub-analysis was performed, comparing immunization rates of children born to mothers treated with antidepressant medications to rates of children born to untreated mothers. Results A total of 709 subjects in the exposed cohort (children born to mothers with post-partum depression symptoms) and 681 subjects in the matched cohort were analyzed. The relative risks among children born to depressed mothers compared with children born to healthy mothers for not receiving any vaccine at 2 months, three doses of pertussis vaccine up to 7 months and four doses of DTaP-Hib-IPV vaccine up to 18 months were 1.15 (95% CI 0.74–1.78), 1.11 (95% CI 0.94–1.31) and 0.82 (95% CI 0.56–1.95), respectively. The relative risks among 139 infants born to treated mothers compared with 570 infants born to untreated mothers for not receiving any vaccine at 2 months, three doses of pertussis vaccine up to 7 months and four doses of DTaP-Hib-IPV vaccine up to 18 months were 1.28 (0.64–2.54), 0.78 (0.57–1.06) and 0.42 (0.17–1.03), respectively. Conclusion We found no significant association between maternal post-partum depression and uptake of child Immunization.